The Use of Synthesized Zinc Oxysulphide Nanoparticles in Phosphate Phosphorus Removal from Synthetic Wastewater and Statistical Analysis - Nilüfer Ülgüdür (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2025)
This study investigated the phosphate phosphorus (PO4-P) removal potential of zinc oxysulfide (ZnOxSy) nanoparticles obtained by fifteen varying component ratios. The statistical meaning of the distinct synthesis compositions was evaluated by regression analysis based on the response of PO4-P removal efficiencies. The results indicated that ZnOxSy nanoparticles could remove PO4-P by 99.5% without optimization of the adsorption process (Initial PO4-P concentration: 15 mg/L, adsorbent dose: 1 g/L, pH: 4.31, contact time: 2 hr). However, the synthesis compositions of ZnOxSy nanoparticles strongly effect the PO4-P removal efficiency. The data could be interpreted by regression analysis with a high R2 of 89.61% and p value of 0.000. The main component that positively affect the PO4-P removal efficiency was hydrogen peroxide, whereas sodium sulfide component had a limited effect.